{Screening for tyrosinase inhibitors from actinomycetes; identification of trichostatin derivatives from Streptomyces sp. CA-129531 and scale up production in bioreactor} - Georgousaki, Katerina; Tsafantakis, Nikolaos; Gumeni, Sentiljana; Gonzalez, Ignacio; Mackenzie, Thomas Andrew; Reyes, Fernando; Lambert, Carole; Trougakos, Ioannis P.; Genilloud, Olga; Fokialakis, Nikolas (Bioorganic {&} Medicinal Chemistry Letters, 2020)
In the course of a primary screening of 614 microbial actinomycete extracts for the discovery of tyrosinase inhibitors, the EtOAc extract of the fermentation broth of the strain Streptomyces sp. CA-129531 isolated from a Martinique sample, exhibited in cell free and cell-based assays the most promising activity (IC50 value of 63 $μ$g/mL). Scaled-up production in a bioreactor led to the isolation of one new trichostatic acid analogue, namely trichostatic acid B (1), along with six known trichostatin derivatives (2-7), four diketopiperazines (8-11), two butyrolactones (12-13) and one hydroxamic acid siderophore (14). Among them, trichostatin A (4) showed six times stronger anti-tyrosinase activity (IC50 2.18 $μ$Μ) than kojic acid (IC50 14.07 $μ$Μ) used as a positive control. Deoxytrichostatin A (6) displayed also strong inhibitory activity against tyrosinase (IC50 19.18 $μ$Μ). Trichostatin A production in bioreactor started together with the exponential phase of growth (day 4) and the maximum concentration was reached at day 9 (2.67 ± 0.13 $μ$g/mL). Despite the cytotoxicity of some individual components, no cytotoxic effect on HepG2, A2058, A549, MCF-7 and MIA PaCa-2 cell lines was found for the EtOAc extract (IC50 {>} 2.84 mg/mL), while it found no cytotoxic against BG fibroblasts at the concentrations were it exerted whitening effect, reassuring its safety and great tyrosinase inhibitory potential.
Keywords: Bioreactor; Enzyme kinetics studies; Secondary metabolites; streptomyces sp; Streptomyces sp.; Trichostatin derivatives; Tyrosinase inhibitors